2007
DOI: 10.1021/om7005084
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic 1H-[1,2]Diphosphole with a Planar Tricoordinated Phosphorus, Plus η2-Coordination Mode between Ruthenium(0) and a Phosphaalkene

Abstract: Tri-tert-butylphenyl)-1H-[1,2]diphosphole (12) was isolated from the unintentional and unexpected dehydrohalogenation of 1,3-bis(chloro(2,4,6-tri-tert-butylphenyl)phosphino)propane ( 5) with DBN. 1H-[1,2]Diphosphole 12 has substantial bond delocalization within the diphosphole system. Remarkably, the shortest P-C bond in the ring (1.725(4) Å) is observed for a nominal P-C single bond with the tricoordinated phosphorus atom. The P-P distance (2.0750(18) Å) in 12 is closer to the value for a PdP bond than for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…Thus, 32 which also exhibited a significantly lowfrequency resonance for P alkene (δ P 23). More recently, Ionkin described a similar situation (δ P 54) for his chelated phosphaalkene complex (Chart 3), 33 the significant shift from the free ligand (δ P 248), which was mirrored in the 13 C data (δ C 67, cf. 181 for the free ligand), being deemed consistent with an η 2 -coordination mode.…”
mentioning
confidence: 70%
“…Thus, 32 which also exhibited a significantly lowfrequency resonance for P alkene (δ P 23). More recently, Ionkin described a similar situation (δ P 54) for his chelated phosphaalkene complex (Chart 3), 33 the significant shift from the free ligand (δ P 248), which was mirrored in the 13 C data (δ C 67, cf. 181 for the free ligand), being deemed consistent with an η 2 -coordination mode.…”
mentioning
confidence: 70%
“…Accordingly, combining all these planarizing effects 1-bis(trimethylsilyl)methyl-3,5-trimethylsilyl-1H-1,2,4-triphosphole [45] is fully planar. Less substituted phospholes, such as 3-methyl-1-supermesitylphosphole [42] and 1-supermesityl-1H-1,2-diphosphole [46] (Fig. 3) are not planar, although the phosphorus pyramid is quite flattened (bond angle sums about the phosphorus are 330°and 348°, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the similarity of the electronic structure of thiophene-oxide to that of phosphole indicates that the inversion barrier of Fig. 3 The structure of 3-methyl-1-(2,4,6-tri-tert-buthylphenyl)phosphole [42], 1-bis(trimethylsilyl)methyl-3,5-trimethylsilyl-1H-1,2,4-triphosphole [45], and 1-(2,4,6-tri-tert-butylphenyl)-1H-1,2-diphosphole [46] this compound can also be reduced by proper substitution, and planar thiophene-oxide derivatives might be designed. In this study the comprehensive characterization of the aromaticity of thiophene-oxide is aimed, in the light of the structural analogy between the phosphino and the sulfuryl group.…”
Section: Introductionmentioning
confidence: 99%
“…Although Mindiola et al have postulated the existence of an intermediary titanium complex 3 bearing a P,N-chelating Schiff-base ligand (Scheme 3) [9], there has been no example for the isolation of a transition metal complex bearing such phosphorus analogue of a -diketiminato ligand [10]. On the other hand, Ionkin et al have reported the attempted synthesis of a phosphorus analogue of -diketiminate 6 bearing 2,4,6-tri-tert-butylphenyl (denoted as Mes*) group [11]. However, it was suggested that 6 undergoes ready intramolecular cyclization to afford 1H- [1,2]diphosphole derivative 5 along with the elimination of Mes*H (Scheme 3).…”
Section: Introductionmentioning
confidence: 99%